Work from home during covid-19: job performance of medical supplies industry officers in Klang Valley - Abd Halim, Nur Atiqah (2021)
Job performance is always a crucial issue in a workplace. Organizations – be it profit or not –profit- insists that employees are the drivers of the organization's success. Without performing well in their job, the employee will influence the organizational performance negatively and reduce its abilities to survive. However, since Malaysia Prime Ministry announced the movement control order (MCO), most organizations had applied for work from home (WFH) policy. The Aon plus survey found that, there was a 30% drop in labour productivity during the outbreak. This is undoubtedly an issue of even more concern when WFH is exercised. Based on the Conservation of resource theory (COR) and related literature review, the current study empirically investigates the factors influencing employee Job performance who work from home in COVID-19 times. A quantitative method was used to analyse data acquired from respondents at medical supplies industry officers in Klang Valley. This study uses a convenience sampling method where 221 respondents responded to the online questionnaire created in the google form. The result was analysed by SPSS to test the hypothesis. Two hypotheses were supported from the Pearson correlation and regression analysis, (Social support and Superior support) while two hypotheses were not supported (Work-family conflict and Work stress). This result reveals that Social support and Superior support have a highly significant relationship with employee job performance. Therefore, authority bodies or policymakers should focus on providing appropriate Social support and Superior support toward employees so that they can perform well even working from home.